Pengaruh Motivasi Kerja dan Masa Kerja Terhadap Efektivitas Kinerja Karyawan Rumah Sakit Bhakti Kartini: The Influence of Work Motivation and Length of Service on Employee Performance Effectiveness at Bhakti Kartini Hospital - Dewi Yuliani; Ratih Hastasari (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
Supportive work motivation can improve employee performance, while a longer length of service can enhance experience and skills. The combination of good work motivation and a long service duration synergistically improves employee performance effectiveness. This study aims to analyze the effect of work motivation and length of service on the effectiveness of employee performance at Bhakti Kartini Hospital. The research method used is a quantitative statistical approach with multiple linear regression techniques and hypothesis testing, namely the T-test and F-test. The sample size consists of 133 respondents, using a probability sampling technique, specifically simple random sampling. The results of this study indicate that work motivation has a partial effect on employee performance effectiveness with a t-value of 2.958 > T-table 1.987 and a significance value of 0.004 < 0.05. Length of service also has a partial effect on employee performance effectiveness with a T-value of 4.831 > T-table 1.987 and a significance value of < 0.001 < 0.05. Meanwhile, both work motivation and length of servic, when considered simultaneously, have an effect on employee performance effectiveness with an F-value of 64.262 > F-table 3.07, and a significance value of < 0.01 < 0.05.